تقويم مناهج كليات التربية بطرابلس ليبيا - قماطى, وفاء أحمد (Ma'ahad al-Tarbiyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2013)
The study aims at evaluating the faculties of education curricula in Tripoli, Libya, in a large sense (objectives, content, instruction, activities, teaching techniques, teaching time, and students' assessment), teachers and students opinions are used as means to collect data and scan the curriculum characteristics (integrity, clarity, convenience, and modernity) which are the principal criteria of evaluation. The researcher applied a descriptive analytic methodology; the participants have been selected through a proportionate stratified sampling. The investigation found there are exists need to review the curriculum content in the faculties of education in order to achieve its objectives. Teachers' evaluation of; integrity, clarity, and convenience criteria was acceptable to some extent, whereas the modernity criteria was poorly evaluated. Furthermore, teachers and students responses differ regarding the extent to which the faculties of education curricula are in accordance with the integrity and modernity criteria. On the other hand, no differences exist among participants regarding the fact that the faculties of education curricula meet the clarity and convenience criteria. In the students' point of view, the scientific resources shortage and the lack of modern teaching techniques are among the most crucial problems. On the lecturers' side, the lack of interest in study from students is among the most crucial problems. Students think that listening, memorization, classification, enhancing linguistic richness, fast reading and comprehension are among the skills that they have well learnt during their period of study in the faculty. However, they extremely and poorly evaluated skills such as abstraction, deduction, discovering connections, using teaching techniques, and inference. Among the most important recommendations that the researcher suggests are; designing and implementing the content of the faculties of education curricula horizontally and vertically, as well as implementing radical changes on the evaluation system in the faculties of education.